Impact of COVID-19 Pandemic on HOME Advantage in Different European Professional Basketball Leagues. Issue 2 (April 2022) - Alonso, Enrique; Lorenzo, Alberto; Ribas, Carlos; Gómez, Miguel Ángel
Our purpose in this study was to examine the impact of the COVID-19 pandemic on home advantage (HA) in sports by comparing European professional basketball games in which spectators were present (pre-pandemic) with "ghost" games in which spectators were absent (during the pandemic). A secondary objective was to analyze how team ability interacted with HA by comparing HA affects pre-pandemic and during the pandemic in the context of differing team ability levels. We used Wilcoxon and Mann–Whitney U tests to identify HA through differences in home win percentages (HW%) between pre-pandemic and pandemic games. Additionally, we ran the Kruskal–Wallis test to identify HA and HW% differences between different team ability levels (high to low). Teams had higher HA and HW% pre-pandemic than during the pandemic. In turn, low level teams presented a higher HA compared to teams at other team ability levels. Thus, low level teams benefited more from playing at their home-court. However, low level teams showed lower HW% than medium and high team ability levels, showing that team ability is more important than HA in determining game outcomes.